1979
DOI: 10.1080/03610737908257223
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in activities of rat hepatocytes. I. Protein synthesis

Abstract: Experiments involving simultaneous comparisons of cells from two animals establish an age-dependent decline in protein synthesis. Specific radioactivities of fractions from cells of aged animals (20+ months) are depressed 60% to 80% versus those from younger animals (2 to 14 months). Isotope ratio patterns derived by PAGE indicate that formation of a 20000 MW polypeptide of cytoribosomal origin is even more strongly and specifically depressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
0
5
1
Order By: Relevance
“…The partial recovery of cell responses may be due to incomplete electroporation efficiency combined with the transient expression or to age-related decrements in general cell functioning such as protein synthesis (52)(53)(54)(55), which is involved in cell motility (15,56) and mitogenesis (35). The ramification of these findings for wound healing are obvious.…”
Section: Discussionmentioning
confidence: 99%
“…The partial recovery of cell responses may be due to incomplete electroporation efficiency combined with the transient expression or to age-related decrements in general cell functioning such as protein synthesis (52)(53)(54)(55), which is involved in cell motility (15,56) and mitogenesis (35). The ramification of these findings for wound healing are obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Much research over the past two decades has focused on the relationship between aging and protein synthesis in the liver. [9][10][11][12] The data generally indicate that total protein synthetic activity in the liver declines with increasing age. Ward 14 studied the age-related changes in the liver protein synthesis of Fischer 344 rats by measuring the valine incorporation rate in the perfused liver.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serum albumin concentrations have been reported to decline in the elderly, suggesting a decline in hepatic protein synthesis with age, 9,10 which many investigators have confirmed experimentally in rodents. 11,12 We investigated the impact of these age-related alterations in liver grafts on post-transplantation liver functions and the growth of young inbred Fisher 344 rat recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Viskup et al (1979) reported that a protein component of ca. 20000 Daltons remained unlabelled by hepatocytes from aged male rats of the Sprague-Dawley strain.…”
Section: (B) Isolated Hepatocytes In Culturementioning
confidence: 94%